INTERNSHIP IN AGRICULTURAL SCHOOLS: AN ALTERNATIVE FOR PUBLIC VOCATIONAL EDUCATION IN STATE OF SAO PAULO - Constantino, Paulo [UNESP]; Poletine, Marcia; Ottoboni de Oliveira, Antonio Carlos (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
Analyzes the maintenance of the internship system for agricultural vocational education in the State of Sao Paulo, from the experience of a public institution, through hybrid survey conducted between 2014 and 2015. Internships offer students the opportunity to obtain their training intensely during a specific period of time within a agricultural school. In this format, the expectation is that students can acquire experience and a more accurate perspective on the profession they have chosen, which will help in the career of maintenance decisions or to deepen the studies, fulfilling the polytechnic and multifaceted perspective.
Keywords: Internship; Vocational Education; Agricultural Education